2020
DOI: 10.1371/journal.pone.0223087
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human T-Lymphotropic Virus (HTLV) and Hepatitis C Co-infection in Bahia, Brazil

Abstract: Both Human T-lymphotropic virus type 1 (HTLV-1) and hepatitis C virus (HCV) are endemic in Brazil. In Salvador, the capital of the state of Bahia, 2% and 1.5% of the general population is infected with HTLV-1 or HCV. This study aimed to estimate the prevalence and the distribution of HTLV/HCV coinfection in Bahia. This cross-sectional study was conducted at the Central Laboratory of Public Health for the state of Bahia (LACEN-BA). All samples in the LACEN database submitted to serological testing for anti-HCV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our study supports previous findings of increased prevalence of intravenous drug use and hepatitis C virus (HCV) co-infection in the HTLV seropositive population ( Murphy et al, 1999 ). Epidemiologic data from Japan and Brazil (in regions endemic for HTLV) have reported HCV co-infection rates in HTLV-1/2 seropositive patients as high as 35.9%, and have suggested transmission routes through transfusions of infected blood products and intravenous drug use ( Nakashima et al, 1994 ; Pinto et al, 2012 ; Pereira et al, 2020 ). A recent meta-analysis of three separate studies of HTLV/HCV co-infection from China, Brazil, and Sweden found a pooled OR of 20.1 ( Rosadas and Taylor, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports previous findings of increased prevalence of intravenous drug use and hepatitis C virus (HCV) co-infection in the HTLV seropositive population ( Murphy et al, 1999 ). Epidemiologic data from Japan and Brazil (in regions endemic for HTLV) have reported HCV co-infection rates in HTLV-1/2 seropositive patients as high as 35.9%, and have suggested transmission routes through transfusions of infected blood products and intravenous drug use ( Nakashima et al, 1994 ; Pinto et al, 2012 ; Pereira et al, 2020 ). A recent meta-analysis of three separate studies of HTLV/HCV co-infection from China, Brazil, and Sweden found a pooled OR of 20.1 ( Rosadas and Taylor, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…HTLV, HCV, and syphilis have similar characteristics: they are sexually transmitted, endemic, and considered a public health problem in Brazil. Their specific mode of transmission facilitates coinfection with other diseases (51)(52)(53). On the other hand, the prevalence rate for HBV in Brazil is low, most likely due to vaccination, which has been available for more than 20 years (54, 55), although there are still unvaccinated individuals at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered intermediate, the rate is higher than that observed in the South and Midwest regions, lower than that observed in the North and Northeast regions, and similar to that observed in the other states of the Southeast region. 9 , 13 , 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…7 Salvador, the capital city of Bahia state, has been identified as the epicenter of HTLV-1 infection in Brazil as 1.48% 8 of its population are infected by this virus, being more prevalent among black/mixed race women, those less educated and, due to the increased likelihood of HTLV acquisition over time, with increasing age. 9 …”
Section: Introductionmentioning
confidence: 99%